Peer Pressure and Productivity: The Role of Observing and Being Observed - Sotiris Georganas; Mirco Tonin; Michael Vlassopoulos (Center for Economic Studies and ifo Institute (CESifo), 2014)
Peer effects arise in situations where workers observe each others' work activity. In this paper we disentangle the effect of observing a peer from that of being observed by a peer, by setting up a real effort experiment in which we manipulate the observability of performance. In particular, we randomize subjects into three groups: in the first one subjects are observed by another subject, but do not observe anybody; in the second one subjects observe somebody else's performance, but are not observed by anybody; in the last group subjects work in isolation, neither observing, nor being observed. We consider both a piece rate compensation scheme, where pay depends solely on own performance, and a team compensation scheme, where pay also depends on the performance of other team members. Overall, we find some evidence that subjects who are observed increase productivity at least initially when compensation is team based, while we find that subjects observing react to what they see when compensation is based only on own performance.
Keywords: D03; J24; M52; M59; 330; peer effects; piece rate; team incentives; real-effort experiment